Alternative of predeportivos games for the initiation sportive of the students in the baseball from the physical education (Orignal) (Revista científica Olimpia, 2017)
The incorporation of girls and boys to the practice of sports is one of the tasks of Physical Education. Therefore, the objective of the research is framed in "To elaborate an alternative of predeportive games that favors the sportive initiation and the projective incorporation of the students to the practice of the Baseball." The investigation was developed in the rural elementary school Arquímides Hill of Mabay in Bayamo, with schoolchildren from 9 to 11. The alternative of predeportive games is a way to encourage sports initiation and the projective incorporation of schoolchildren to the practice of Baseball in the Physical Education class and Sports for All.
Keywords: Alternative; Physical Education; Sport for All; Sportive Initiation; Predeportive Games; Projective Incorporation